A Survey of Multiple Interactions Between Plants and the Urban Environment - Fineschi, Silvia; Loreto, Francesco (Frontiers in Forests and Global Change, 2020)
It is well acknowledged that plants in urban areas provide multiple ecosystem services. They contribute improving ambient quality and mitigating negative impacts of human presence, beautifying the anthropic environment, and promoting place identity and cultural heritage. However, the existence of plants in general, and trees in particular, cannot be considered independent on urban activities and infrastructures. Release of plant volatile compounds is profoundly affected in urban environments, in turn modifying plant relationships with other living organisms, both plants and animals, and affecting air chemistry and quality. Plants also interfere with stone artifacts, cultural and historical heritage. Plant-human coexistence requires precise and adequate managing measures, which have often been ignored in cities’ government and planning. Plants and humans (and human’s infrastructures) are frequently considered as independent from each other and plant requirements are often disregarded, thus causing difficult or erroneous management and/or environmental damage. We review some of the most important ecosystem services provided by plants in urban environment, and also focus on possible negative effects of plants that may become relevant if urban vegetation is improperly managed and unintegrated in proper city planning, both of historical centers and of recent or new neighboroughs.